Uses of Nanoparticles in Photo Catalysis: Exploring the Boundless Potential of Nanoparticle-Enhanced Photo Catalysis (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The aim of this review paper is to give an overview of the development and implications of nanotechnology in photo catalysis. The topics covered include a detailed look at the unique properties of nanoparticles and their relation to photo catalytic properties.